(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the methodological side of the notion “pedagogical conditions”. The opinions of modern researchers about the notion “pedagogical conditions” have been considered. As well the definitions for forming the pedagogical conditions for students dly culture have been given.